Dihydroartemisinin alleviates deoxynivalenol induced liver apoptosis and inflammation in piglets - Jibo Li; Yongsong Bai; Kaidi Ma; Zhongshuai Ren; Jianping Li; Jing Zhang; Anshan Shan (Ecotoxicology and Environmental Safety, 2022)
Deoxynivalenol (DON) is one of the mycotoxins that contaminate cereals and feed, thereby endangering human and animal health. Dihydroartemisinin (DHA), a derivative of artemisinin, has anti-inflammatory and antioxidant functions in addition to anti-malaria and anti-cancer. The purpose of this study was to investigate the effects of DHA on alleviating liver apoptosis and inflammation induced by DON in piglets. The experimental design followed a 2 (normal diet and DON-contaminated diet) × 2 (with and without supplementation of DHA) factorial arrangement. 36 weaned piglets were subjected to a 21-day experiment. Results showed that DON increased ALT activity, the levels of TNF-α, IL-1β and IL-2, and reduced the levels of total protein (TP) and albumin (ALB) in the serum. However, DHA decreased the levels of TNF-α, IL-1β and IL-2, and increased the levels of TP and ALB. Also, DON decreased glutathione (GSH) content and catalase (CAT) activity, and increased methane dicarboxylic aldehyde (MDA) content. But GSH content was increased by DHA. In addition, DHA decreased DON-induced increase in apoptosis rate of hepatocytes. Furthermore, DON activated death receptor pathway to promote apoptosis by up-regulating the protein expression of FasL and caspase-3, and the mRNA expression of FasL, TNFR1, caspase-8, Bid, Bax, CYC and caspase-3. However, DHA reduced caspase-3 protein expression, as well as the mRNA expression of FADD, Bid, Bax, CYC and caspase-3. Besides, DON also activated TNF/NF-κB pathway to induce an inflammatory response by up-regulating TNF-α protein expression, and the mRNA expression of TNFR1, RIP1, IKKβ, IκBα, IL-1β and IL-8. Nevertheless, DHA reduced the mRNA expression of RIP1, IκBα, NF-κB, IL-1β and IL-6, and the protein expression of TNF-α and NF-κB. In conclusion, DHA improved DON-induced negative effects on serum biochemical parameters and inflammatory cytokine levels, hepatic antioxidant capacity, hepatic apoptosis and inflammation.